2015
DOI: 10.1016/j.commatsci.2015.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of reactive force fields for prediction of the thermo-mechanical properties of cellulose Iβ

Abstract: a b s t r a c tMolecular dynamics simulation is commonly used to study the properties of nanocellulose-based materials at the atomic scale. It is well known that the accuracy of these simulations strongly depends on the force field that describes energetic interactions. However, since there is no force field developed specifically for cellulose, researchers utilize models parameterized for other materials. In this work, we evaluate three reactive force field (ReaxFF) parameter sets and compare them with two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…Results correspond to a typical mineral content of 70 wt%. a) I) Adapted with permission . Copyright 2015, Elsevier.…”
Section: Multiscale Modelingmentioning
confidence: 99%
“…Results correspond to a typical mineral content of 70 wt%. a) I) Adapted with permission . Copyright 2015, Elsevier.…”
Section: Multiscale Modelingmentioning
confidence: 99%
“…The ReaxFF force field was based on the parameter set developed for glycine conformers and glycine–water complexes . It has been reported that the ReaxFF force field is able to predict some properties of cellulose with reasonable accuracies: lattice constants and angles (deviations from experimental values between <1 and ~6%), elastic constants (within the range of experimental values) and thermal expansion (within the range of experimental values for one direction but not for two other directions) . The Young's moduli of crystalline cellulose predicted using the ReaxFF force field are about 190 and 30 GPa for the directions parallel and perpendicular to the cellulose axial direction, respectively .…”
Section: Model and Simulationmentioning
confidence: 99%
“…The molecular structures of the anions and cations from the ILs considered in this work are shown in Figure 2 Figure 2 illustrates the hydrogenbond network in cellulose I β (the most abundant crystal structure), 83 [EMTr 124 ][OAc] was synthesized from 1-methyl-1,2,4-triazole (received from abcr GmbH). The synthesis involved an alkylation with ethyl bromide, methyl iodide, methyl triflate, or N-methyl-bistriflamide as the first step, which was followed by anion exchange with silver acetate (received from Alfa Aesar) in methanol to obtain the acetates.…”
Section: ■ Introductionmentioning
confidence: 99%